Analysis and Design of Production Schedulling System for CV. Bulu Nusantara Gresik - Emmy Wahyuningtyas (JEECS (Journal of Electrical Engineering and Computer Sciences), 2017)
CV. Bulu Nusantara is a company located in Gresik – East Java produces some kinds of flour as animal feedingredients. The flours are come from chicken feathers, chicken bones, fishes and clams. The company has limitedproduction machinery, so as to produce each kind of flour for optimum results, it must be well planned. This study isto analyze and design the information system needed by the company. The system is designed to manage inputs,processing them and resulting some informations like Master Production Schedule, dayly/weekly/monthly productionreport, and so on. The analysis phase produces two algorithms, each for estimating the order finishing time andschedulling calculation. The design phase produces context flow diagram, first level of data flow diagram, theconceptual and physical data model. The study result is showing us that the company needs the information systemwhiches consist of seven interrellated entities, eight main processes and flexible period of detailed reporting or resumereporting in form of chart.